2015
DOI: 10.15252/embj.201591552
|View full text |Cite
|
Sign up to set email alerts
|

BH 3‐in‐groove dimerization initiates and helix 9 dimerization expands Bax pore assembly in membranes

Abstract: Pro-apoptotic Bax induces mitochondrial outer membrane permeabilization (MOMP) by forming oligomers through a largely undefined process. Using site-specific disulfide crosslinking, compartment-specific chemical labeling, and mutational analysis, we found that activated integral membrane Bax proteins form a BH3-in-groove dimer interface on the MOM surface similar to that observed in crystals. However, after the a5 helix was released into the MOM, the remaining interface with a2, a3, and a4 helices was rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
132
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 65 publications
(159 reference statements)
15
132
3
Order By: Relevance
“…Therefore, Bax dimers and oligomers could facilitate lateral sorting in the OMM or the formation of Bcl-2 protein-containing complexes (52). TMD-TMD interactions are consistent with models of Bax activation, suggesting separation of helices α5 and α6 (27,53) and the concerted insertion of both helices into the OMM (51,54). Conversely, Bax activation according to the clamp model would require a sequential mechanism to allow formation of antiparallel TMD interactions (28).…”
Section: Resultsmentioning
confidence: 61%
“…Therefore, Bax dimers and oligomers could facilitate lateral sorting in the OMM or the formation of Bcl-2 protein-containing complexes (52). TMD-TMD interactions are consistent with models of Bax activation, suggesting separation of helices α5 and α6 (27,53) and the concerted insertion of both helices into the OMM (51,54). Conversely, Bax activation according to the clamp model would require a sequential mechanism to allow formation of antiparallel TMD interactions (28).…”
Section: Resultsmentioning
confidence: 61%
“…However, how BAK and BAX homodimers multimerize is unknown. From linkage or proximity measurements based on electroparamagnetic resonance and double electron-electron resonance various secondary interfaces have been implicated to allow homodimers to associate (23)(24)(25)(26)(27)(28). Alternatively, based on linkage analysis and mathematical modeling, random aggregation of homodimers has also been proposed (29).…”
mentioning
confidence: 99%
“…A new interface for Bax dimerization was identified which occurs via the α9:α9 helices within the membrane apart from the BH3:groove interface found on the surface, which was shown to be crucial for pore expansion (Zhang et al 2015). From this study, the discovery of another feature required for Bax dimerization has demonstrated that studies on the dynamics of protein structure and interactions are required to fully understand apoptosis at the dynamic membrane interface.…”
Section: Mode 1 Inhibiɵonmentioning
confidence: 93%
“…Upon α9 membrane insertion, rearrangement of the helices resulted in the BH3-in-groove dimerization at the MOM surface. The α9 helix that transverses the membrane interacts with α9 of another monomer to cause the pore expansion (Zhang et al 2015). These conformational changes were only able to be observed in the presence of membrane, thus emphasizing the importance of the membrane for the whole MOMP process.…”
Section: Biophysical Analysis Of the Apoptotic Pore Structural Modelsmentioning
confidence: 97%
See 1 more Smart Citation